Impact of Training and Development on Employee Engagement in Nepalese Commercial Banks (Nepalese Journal of Management Research, 2025)
The purpose of this research is to examine the relationship between training and development and employee engagement in Nepalese commercial banks. This cross-sectional study employs a causal-comparative research design grounded in positivist assumptions. A survey of 384 bank employees from 10 commercial banks was conducted, and the data were analyzed using statistical package for social science (SPSS) to assess the relationship. The results reveal that training efficiency, leadership support and work alignment are significantly and positively associated with employee engagement. This study provides a clear direction to a variety of practitioners in the commercial banking industry. Developing and preserving sympathetic and emotional relationship with team members, supervisors, and other higher-ranking employees can aid in enhancing employee engagement. Business managers and planners can use this knowledge to concentrate their efforts on developing employer training practices that will effectively engage employees. This study empirically investigates the relationship between training and development practices and employee engagement in the commercial banking sector in Nepal. The findings provide valuable insights for bank management, suggesting how strategic training and development practices significantly enhance employee engagement.